Teaching writing skills, case study: caleb - Martínez Pico, María Fernanda (2023)
Currently, the educational system is undergoing constant transformation. The imminent need for structural changes and pedagogical strategies focused on virtual education posed a challenge during the pandemic. However, these adaptations that were carried out have evolved into a broad field of action and research, with the focus being on teaching communication and language skills such as reading and writing. The school is the place where both students and teachers interact in pairs, constructing the meaning of learning and teaching processes through a fundamental tool: classroom interaction (Cantillo Hoyos & Gregorio Calabria, 2021). Pedagogical support is a useful strategy that combines educational research, practice, and teacher reflection, with the joint goal of enhancing the knowledge imparted to students......